Analysis of the Try Out Problem for the National Examination of Natural Sciences Physics Type HOTS - Heryanto, Wawan Prasetyo; Supriyadi, Supriyadi; Darsono, Teguh (Universitas Negeri Semarang, 2020)
This research's aim is to know about HOTS questions of Physics in try out of National Examination and HOTS's students of Junior High School Muhammadiyah 1 Wonosobo. The research type was descriptive research, and the research used analysis technique. This technique is done by analyze question documents and students' answer sheet of trying out of Physics National Examination HOTS students of Muhammadiyah 1 Wonosobo junior high school. The subjects in this study were students of class IX Muhammadiyah 1 Wonosobo junior high school in the academic year 2019/2020 with 126 students. The data obtained in the form of a percentage of HOTS type questions and the percentage of students absorption of the results of working out the try out problem. Based on the analysis of the data that has been done, obtained by the category of HOTS is 23.5%, namely in the C4 aspects and the absorption of students by 28.5% with the category is not good. Therefore, it can be concluded that type of HOTS questions in the tryout of Physics National Examination has poor distribution.